Synthesis Of Free Standing Anodic Zro2 Nanotubes In Potassium Carbonate Ethylene Glycol Electrolyte For Photocatalyst Application - Soaid, Nurul Izza (2019)
ZrO2 nanotubes were successfully synthesis by using anodisation method. Mixture of ethylene glycol (EG) with ammonium fluoride (NH4F) produced coral-like structures morphology of ZrO2. Lack of oxygen provider in electrolyte limit the growth of ZrO2 nanotubes using anodisation method. Therefore, addition potassium carbonate (K2CO3) solution as oxygen provider in the anodic electrolyte enhanced the growth of ZrO2 porous structure to nanotubular structure. Increasing from 0.5 vol % to 4 vol % of K2CO3 in anodic electrolyte, the length of nanotubes increased from 8 to 20 μm as the K2CO3 in anodic electrolyte. Average diameter of the ZrO2 nanotubes about 60 to 80 nm. Besides, addition of K2CO3 lead to the formation of loose ZrO2 flakes as so-called free-standing ZrO2. The free-standing ZrO2 achieved by shorter time frame compared to others work. The advantages of free-standing ZrO2 can be used as catalyst for wastewater treatment such as photocatalyst application. In this work, as anodised free-standing ZrO2 were used to evaluate its photocatalytic activity towards methyl orange (MO). The results were compared with annealed free-standing ZrO2. The annealing temperature studied is in the range of 200 to 800 °C. As-anodised samples showed the best degradation which around 70 % compared to anneal samples only degraded around 40 %